IMPLEMENTATION OF FINANCIAL GOVERNANCE IN ISLAMIC EDUCATIONAL INSTITUTIONS OF MADRASAH IBTIDAIYAH IN MEDAN - Siregar, M. Fajri Syahroni (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2023)
Financial Governanceis a policy that regulates and controls financial operations by protecting rights through controlling the company's operational processes to achieve company goals based on the provisions of Allah SWT. This study aims to look at the implementation of Financial Governance carried out at Islamic Education Institutions Madrasah Ibtidaiyah in Medan. This study uses a qualitative descriptive approach using primary data (through interviews and distributing questionnaires) and secondary data). The results of the study show that the Madrasah Ibtidaiyah Islamic Education Institution has implemented Financial Governance through the Good Corporate Governance approach and the addition of Shariah Complience indicators to this implementation.